Mapping the Return of Argentine Researchers - Bayle, Paola Adriana (2015)
Since 2003 the Argentine government runs the RAÍCES Programme (Network of Argentine Researchers and Scientists Abroad). This programme has been designed to mitigate the negative effects of the loss of skilled human resources. This study will address one of the main programme results of the RAÍCES Programme: the return of an important group of Argentine researchers who reinserted themselves into the main national agency dedicated to the promotion of scientific research in Argentina, that is, the National Council for Scientific and Technical Research (CONICET, for its Spanish acronym). We will attempt to draw a map of their repatriation, giving some insights into its structural dynamics and highlighting the characteristics of the returnees using a statistical approach. At the same time, we will link different variables in order to understand different itineraries of returnees in the Argentine university scientific field that help us explain this geography